The Effectiveness of Trisula Motivation Model-based Classroom Guidance to Improve Students’ Self-directed Learning (Jurnal Bimbingan Konseling, 2020)
This study aimed at identifying and analyzing the trisula motivation model-based classroom guidance to improve students’ self-directed learning. It used pretest and multiple posttest design. In details, purposive sampling technique was used to divide 124 experimental subjects into two groups randomly with each group containing 62 students. Meanwhile, the researchers used self-rating scale of self-directed learning (SRSSDL) to collect the data. The results of repeated measures ANOVA of the experimental group after receiving the intervention showed that the trisula motivation model-based classroom guidance was effective to improve students’ self-directed learning (F (1.92) = 4.29; p <0.05), while the control group that did not get the intervention gained ( F (1.81) = 0.06; p> 0.05). This study confirmed that the trisula motivation model-based classroom guidance is effective to improve students’ self-directed learning.